Transition programs in Philippine setting and expectations of parents of students with down syndrome - Yambao, Emelda Tecson (2006)
This descriptive and associational study identified the expectations of parents and the relationship of their socio-demographic profile with these expectations, on transition programs for Students with Down Syndrome (SWDW). The subjects consisted of thirty SWDS aged 14 and above. The respondents composed of 30 parents and 17 teachers accomplished self-administered questionnaires for information on parental expectations and transition program of schools. Parents of educable SWDS have higher expectations than parents of trainable SWDS. Their expectations include independence skills development on different aspects needed for a regular person's life. These are congruent with transition programs except in social skills and self-care skills domains.